E-MODUL AERODROME FLIGHT INFORMATION (AFI) PROCEDURE BASED ON LEARNING MANAGEMENT SYSTEM (LMS) - Jeremiah Ezekiel, Jabez; Ratna Sari, Dewi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The framework of the Aerodrome Flight Information (AFI) Procedure e-module will be based on the Aerodrome Flight Information (AFI) Procedure Semester Learning Plan of Poltekbang Surabaya. For theoretical and practical references, the e-module will draw from both international and national documents. The result of this research is an Aerodrome Flight Information (AFI) Procedure e-module that can be used for the cadets’ learning process in the Aerodrome Flight Information (AFI) Procedure course. The e-module contains learning materials presented through written content, images, audio, and videos. The purpose of this study is to be used and practiced in learning, to add variety in learning and to increase preparation before On the Job Training (OJT).